The Journey Continues: Highlights from the 2024 ASMA Conference - Marshall Magnusen (Journal of Applied Sports Management, 2024)
The Journal of Applied Sport Management (JASM) is the official publication of the Applied Sport Management Association (ASMA), which is a scholarly organization that builds research partnerships between faculty and students. ASMA also facilitates connections between sport management faculty and students studying sport and practitioners working in the sport industry. In 2023, the annual conference was hosted by Samford University under the direction of Dr. Patrick Marsh. With 300 registrants, the 2024 conference was the most attended in ASMA history. It took place in Knoxville, Tennessee. Hosted by the University of Tennessee, the conference was spearheaded by Drs. Adam Love and Rob Hardin. The 2025 conference will be hosted by the University of Cincinnati. Several highlights from the most recent conference are noted below.
Keywords: association; management; sport; students